Impact of a prescription drug monitoring program use mandate on potentially problematic patterns of opioid analgesic prescriptions in New York City - Bachhuber, Marcus A. (Pharmacoepidemiol Drug Saf, 2019)
PURPOSE: To evaluate New York State’s mandate that prescribers query the prescription drug monitoring program (PDMP) prior to prescribing Schedule II–IV medications. METHODS: We conducted an interrupted time series analysis of opioid analgesic prescriptions dispensed to adult New York City (NYC) residents using data from New York State’s PDMP. Our main outcomes were the rate of (a) greater than or equal to five prescriber episodes, (b) greater than or equal to five prescriber and greater than or equal to five pharmacy episodes, and (c) paying for prescriptions with both cash and insurance, per quarter, per 100 000 NYC residents. We defined three periods: (a) the baseline period (January 2011 to July 2012), (b) the anticipatory period (September 2012 to July 2013) after mandate law enactment but before mandate implementation, and (c) the postmandate period (September 2013 to December 2015). For each outcome, we used autoregressive linear regression models to account for correlation in outcomes over time. RESULTS: At the end of the postmandate period, the rate of greater than or equal to five prescriber episodes was 58% lower than expected (absolute difference: −17.2 per 100 000 NYC residents; 95% CI, −31.2 to −3.1), the rate of greater than or equal to five prescriber and greater than or equal to five pharmacy episodes was 88% lower than expected (absolute difference: −8.6; 95% CI, −11.0 to −6.3), and the rate of cash and insurance payment episodes was 50% lower than expected (absolute difference: −145.4; 95% CI, −279.4 to −11.6). CONCLUSIONS: While outcomes were relatively rare, New York State’s PDMP mandate was associated with significant decreases in rates of potentially problematic patterns of opioid analgesic prescriptions.